Information and uncertainty: Utilizing the pediatric oncology functional communication model to better understand early AYA survivorship and late effects communication - Carpenter, Kendall; Berenblum Tobi, Catalina; Levy, Lydia Haupt; Revette, Anna C.; Kenney, Lisa B.; Vrooman, Lynda M.; Greenzang, Katie A. (Patient education and counseling, 2026)
To explore the communication preferences of adolescents with cancer regarding the discussion of survivorship and late effects (LE) and to identify key communication functions and areas for improvement in LE communication. This qualitative secondary analysis applied the adolescent oncology functional communication model to 17 semi-structured interviews conducted with adolescents (aged 12–22 years) to understand their LE communication preferences. Purposive sampling identified participants undergoing cancer treatment or who had completed pediatric cancer treatment within the past five years. Interviews occurred between April 2022 and April 2023; they were audio-recorded, transcribed, and individually coded. Thematic analysis identified themes that emerged within the communication functions. Participants identified "exchanging information" and "managing uncertainty" as critical functions in survivorship communication, but highlighted areas for improvement. Many adolescents appreciated receiving information early, however the volume of content was overwhelming, and some felt unprepared for survivorship despite information. Adolescents emphasized the importance of mental health support and peer validation, pointing to gaps in psychosocial resources and the desire for more shared experiences with fellow survivors. Modifiers to communication preferences which influenced how adolescents wanted to receive information about late effects included the phase of treatment (active treatment vs. survivorship), individual learning preferences, existing parent-child dynamics, and diagnosis/prognosis. Utilizing communication functions as a framework allowed us to better understand adolescent preferences and identify areas for improvement within early communication about survivorship and LEs. Understanding the modifying factors that influence adolescent preferences will help tailor communication strategies to better meet their needs. This study applied a validated framework to survivorship and late effects communication with adolescents, a vulnerable patient population in pediatric oncology, highlighting important areas for improvement. The findings can be utilized to guide future adolescent- specific interventions aimed at improving adolescent engagement in survivorship care and risk-based screening. •AYAs value early survivorship info but report feeling overwhelmed at diagnosis.•Communication about late effects helps manage uncertainty but gaps remain.•Mental health impacts are often under-addressed in early survivorship talks.•Communication preferences vary by treatment phase, diagnosis, and family dynamics.•Peer support and tailored strategies may improve AYA survivorship engagement.